Risk Assesment Pada Pekerjaan Pengambilan Contoh Uji Di PT. XYZ - Mohamad Nurhamzah Ramadani; Merry Sunaryo; Friska Ayu; Ratna Ayu Ratriwardhani (Peneliti.net, 2022)
Good occupational health and safety (K3) needs to be done in an effort to reduce the possibility of accidents when doing work. To reduce the number of work accidents, it is necessary to control risk in the workplace through risk management, one of the methods is HIRARC. PT XYZ is a company engaged in providing environmental laboratory services. This company has several fields namely administration, analyst, test sample taker. Thearea most at risk is the part of the test sample taker. The purpose of this study is a Risk Assessment on the work of taking test samples at PT. XYZ. This type of research is qualitative with descriptive observational method, by describing the results of hazard identification and risk assessment on the work of taking test samples, in order to obtain a recommendation for hazard risk control using the HIRARC (Hazard Identification Risk Assessment Risk Control) method. Data collection techniques were carried out by observation, in-depth interviews and documentation. Sampling work carried out by test sampling officers PT. XYZ has 26 potential hazards. Test sample taker officer PT. XYZ has a low including the risk of skin irritation, eye irritation, minor injury, moderate includes the risk of muscle pain, fractures.and high includes the risk of injury to death, fire, heat stress, dehydration, respiratory infections. The recommended control refers to the control hierarchy, namely elimination, substitution, engineering, administrative and personal protective equipment. The conclusion of the test sampling job shows that the hazard identification stage of this work produces 26 potential hazards and has a risk level of low, moderate, high. The recommended risk control that has the most priority is the implementation of the OHS management system because the company is required to apply 64 basic criteria